Respuesta :

Answer:

see explanation

Step-by-step explanation:

([tex]\sqrt{3}[/tex] + [tex]\sqrt{2}[/tex] )²

= ([tex]\sqrt{3}[/tex] + [tex]\sqrt{2}[/tex] )([tex]\sqrt{3}[/tex] + [tex]\sqrt{2}[/tex] )

Each term in the second factor is multiplied by each term in the first factor , that is

[tex]\sqrt{3}[/tex] ([tex]\sqrt{3}[/tex] + [tex]\sqrt{2}[/tex] ) + [tex]\sqrt{2}[/tex] ([tex]\sqrt{3}[/tex] + [tex]\sqrt{2}[/tex] ) ← distribute parenthesis

= 3 + [tex]\sqrt{6}[/tex] + [tex]\sqrt{6}[/tex] + 2 ← collect like terms

= 2[tex]\sqrt{6}[/tex] + 5

--------------------------------------------------------

(b)

(2 - [tex]\sqrt{5}[/tex] )(2 + [tex]\sqrt{5}[/tex] )

= 2(2 + [tex]\sqrt{5}[/tex] ) - [tex]\sqrt{5}[/tex] (2 + [tex]\sqrt{5}[/tex] ) ← distribute parenthesis

= 4 + 2[tex]\sqrt{5}[/tex] - 2[tex]\sqrt{5}[/tex] - 5 ← collect like terms

= - 1